The Development of “Batik Sendang” and Integrated Marketing Communication Strategy using a Mathematical Model Approach - Nur Ilmayasinta; Novitasari Novitasari; Ayu Fita Sari (UNIVED Press, 2024)
The aim of this research are to ascertain, investigate, and evaluate the degree to which the creation of innovative economic products for Sendang Paciran batik clothing and the use of an integrated marketing communication strategy have an impact on the tourism appeal of Sendang Agung and Sendang Duwur Villages Paciran District. The explanatory survey method is employed in this research. The results of the research show that even though the villages of Sendang Agung and Sendang Duwur Paciran have built an integrated marketing communication plan for creative economic products, more work has to be done on it. This is evident from the responses of the vast majority of respondents who concurred with the posed questions. However, of the four forming parts of integrated marketing communications, public relations, publicity, and advertising are the forming factors with the strongest role and are the ones that have been executed the best.